(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The global refugee crisis exposes profound failures in existing recognition systems, which remain focused on verifying lost credentials rather than valuing the skills and capacities refugees acquire through displacement. This article introduces REGEN (REfugeesGENeration), a regenerative recognition framework that leverages artificial intelligence to surface, validate, and align refugees’ informal and experiential learning through narrative-based skill discovery and adaptive assessment. By combining AI-enabled discovery, standards-based alignment, and the issuance of verifiable digital credentials as a global common good, REGEN reframes recognition from gatekeeping to pathway creation. The article argues that ethically governed, community-driven AI systems can transform recognition into an instrument of empowerment, unlocking human potential while delivering substantial social and economic benefits for host societies. Keywords: refugee recognition; artificial intelligence; recognition of prior learning; digital credentials; verifiable credentials; global mobility; skills recognition; lifelong learning; equity and empowerment; open recognition